Frontline Nursing Care: The COVID-19 Pandemic and the Brazilian Health System - Alisson Fernandes Bolina RN, MSc, PhD; Emiliana Bomfim RN, MSc; Luís Carlos Lopes-Júnior RN, OCN, MSc, PhD (SAGE Publishing, 2020)
Emerging and reemerging infectious diseases are constant challenges for global public health. After the World Health Organization declared COVID-19 a pandemic on March 11, 2020, the spread of SARS-CoV-2 has been the focus of attention for scientists, governments and populations worldwide. In Brazil, the first case of COVID-19 was identified on February 26 2020, being the first country in Latin America to have affected patients. Almost four months later, more than one million confirmed cases of COVID-19 have been identified in the country, and the virus has spread across all 27 states and is responsible for at least 48,954 deaths until June 19, 2020. In addition, a global outbreak requires the active participation of the nursing workforce in clinical care, education, and sharing of accurate information of public health and policies. This year is particularly important for Nursing, as 2020 is the international year for Nursing and Midwifery Professionals. Nursing professionals corresponds to more than half of the health workforce in the country, being crucial in implementing public health policies and programs. Nurses and frontline health care workers have a critical role in the COVID-19 prevention and response, not only by providing direct assistance to patients and communities, but also in the implementation of health promotion and prevention strategies. Hence, we provide a reflection on the strengths and weaknesses of how the nursing profession is engaged with the COVID-19 response in Brazil.